Prediksi Harga Rumah Di Jabodetabek Menggunakan Metode Artificial Neural Network - Hafizh, Muhammad Abdullah; Subairi, Subairi; Libriawan, Raditya Dimas; Maulana, Naufal Duta; Rizki, Agung Mustika (Institut Teknologi Adhi Tama Surabaya, 2024)
A house is a fundamental need for humans. Determining house prices is a crucial aspect of property transactions, especially in major areas like Jabodetabek, where property prices are consistently rising. Prediction is a suitable tool to assist in decision-making for determining house prices. There are numerous methods that can be applied for prediction; the author employs the Artificial Neural Network (ANN) method. ANN is known as a highly flexible predictive algorithm capable of accommodating various input features. The results of using the ANN method for predicting house prices in the Jabodetabek area show a Mean Absolute Error (MAE) of 0.209, Mean Squared Error (MSE) of 0.159, and Mean Absolute Percentage Error (MAPE) of 4.951.